Miguel Antonio Caro and the (Trans)Formations of Classical Tradition in Colombia - Bernadó Ferrer, Gemma (Pnyx: Journal of Classical Studies, 2022)
This paper highlights a unique phenomenon in Colombia, the entanglement between Latin and power, epitomised by the pivotal role of President and Latinist Miguel Antonio Caro. The study of Classics arrived in the territory with the first conquerors from Spain at the end of the 16th century and Caro stands on the shoulders of a long Classical tradition in New Granada. A member of the Conservative Party and a humanist, he was widely known for his work and contribution in the Political Constitution of the Republic of Colombia of 1886 and his central role in the formation of the modern state of Colombia. Besides politics, Caro co-authored a Latin Grammar, wrote many articles on translation and Latin Literature, composed poetry in Spanish and Latin, and produced the first translation of the complete works of Vergil in Spanish. Caro’s works and days aptly demonstrate the association between grammar, Classics, and state power throughout the history of Colombia. The paper contextualises the role of Classics from the colonial period until the end of the 19th century and sketches Caro as an individual and a politician. It outlines his scholarly activity, which involved grammar, translation, and scholarly publishing, and underlines his influence on other scholars and his idiosyncratic interest as a decisive political figure in re-invigorating interest in Latin language and literature.